2019
DOI: 10.1111/ane.13180
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after stroke: A Swedish nationwide registry‐based study

Abstract: ObjectivesA substantial proportion of individuals with stroke are of working age. After stroke, it is important to return to work (RTW), both for the individual's satisfaction with life and economically for society. The current comprehensive, long‐term study aimed at investigating in what time period the RTW continues after stroke and what factors could predict RTW.Materials and methodsAll individuals registered in the registry Riksstroke with stroke in Sweden at ages 18‐58 years during 2011 were eligible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…13 Post-stroke fatigue is one of the most disabling symptoms in stroke survivors; it reduces the quality of life, increases mortality, and is a barrier to stroke rehabilitation, and has also been shown to affect patients' return to working life. 14,15 In addition, health professionals still lack a regimen or a coping strategy to equip the patient with at discharge from hospital. 16 Efficient management of post-stroke fatigue should be a priority in stroke rehabilitation given the incidence of stroke and the prevalence and detrimental impact of poststroke fatigue on independent living and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…13 Post-stroke fatigue is one of the most disabling symptoms in stroke survivors; it reduces the quality of life, increases mortality, and is a barrier to stroke rehabilitation, and has also been shown to affect patients' return to working life. 14,15 In addition, health professionals still lack a regimen or a coping strategy to equip the patient with at discharge from hospital. 16 Efficient management of post-stroke fatigue should be a priority in stroke rehabilitation given the incidence of stroke and the prevalence and detrimental impact of poststroke fatigue on independent living and overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…1 In particular, if a working-age person suffers a stroke, the poststroke effects may reduce work performance. 2 Recently in Japan, Saeki et al reported that the proportion of stroke survivors who have had a successful return-to-work (RTW) experience has remained static at 45% for the past 20 years. 3 According to previous studies, important factors associated with RTW and stroke are gender, age, enterprise size, education level, stroke severity, and comorbidity.…”
Section: Introductionmentioning
confidence: 99%
“…3 According to previous studies, important factors associated with RTW and stroke are gender, age, enterprise size, education level, stroke severity, and comorbidity. 2,4,5 In addition, the potentiality of RTW after hospital discharge was reported to be influenced by impairments and occupation. 6 In particular, poststroke survivors have residual impairments in the upper and lower limbs (hemiparesis), which are important factors related to RTW.…”
Section: Introductionmentioning
confidence: 99%
“…Lower educational level is an independent predictor of RTW during the early post-stroke years in Sweden and Korea. [30][31][32] The increased odds of those with lesser education not returning to work implies types of occupation affected (white vs blue collar) and the correlating job demands and possible job modifications. A physicalfocused occupation may not have much room for modification to accommodate the stroke survivor's abilities.…”
Section: Discussionmentioning
confidence: 99%